Directive Speechs Acts Short Sto Directive Speechs Acts Short Story Who Ate the Bread by Ana sakinah - Iis istikomah Sanuri (Merwin Publisher, 2026)
This study investigates directive speech acts in the short story “Who Ate the Bread?” by Ana Sakinah using a qualitative descriptive approach grounded in Searle’s speech act theory. While previous studies on directive speech acts have predominantly focused on conversational or real-life discourse, this study offers a novel perspective by examining how directive speech acts operate within a literary narrative to construct meaning and characterize interpersonal relationships. Directive speech acts, defined as utterances intended to influence the actions or behavior of the hearer, include commands, requests, advice, and warnings. The objectives of this study are to identify the types of directive speech acts and to analyze their pragmatic functions in the context of the story. The findings reveal that four types of directive speech acts are employed, with commands emerging as the most dominant form, particularly in interactions involving Han’s father. These speech acts are realized through both direct and indirect strategies and are significantly shaped by contextual factors such as authority, emotional proximity, and social roles. Importantly, this study demonstrates that directive speech acts in literary texts are not merely communicative tools but also serve as narrative devices that contribute to character development, plot progression, and the articulation of moral values, including parental love, obedience, belief, and human vulnerability. This study contributes to the field of literary pragmatics by highlighting the functional role of directive speech acts in shaping narrative meaning and offering a deeper understanding of how language as action operates within fictional discourse. It also expands the application of speech act theory beyond everyday communication into the analysis of literary texts.